Use of Solar Panels for Shade for Holstein Heifers - Ana Flávia P. A. Faria; Alex S. C. Maia; Gustavo A. B. Moura; Vinícius F. C. Fonsêca; Sheila T. Nascimento; Hugo F. M. Milan; Kifle G. Gebremedhin (Animals, 2023)
Animal Agrivoltaics combines electric energy generation, animal thermal comfort, and sustainable production at the same time. This model of production can foster the sustainable intensification of dairy production in tropical areas where solar irradiance is high and nearly constant throughout the year. In this study, we propose Animal Agrivoltaics as an alternative practice to reduce the heat load and eCH4 emissions from dairy heifers in tropical areas. To attest this hypothesis, (1) the meteorological data and the behavioral and physiological responses of the animals were integrated in order to determine the benefits provided by the shade from the solar panels on the thermoregulation of the dairy heifers, and (2) measurements of the enteric methane emissions were taken to determine the potential of the solar panels to offset the GHG. Seven crossbred Holstein heifers (7/8, Holstein × Gyr) with a mean body weight of 242 kg (SD = 53.5) were evaluated in a paddock shaded with ten modules of solar panels. Miniature temperature loggers were used to record the body surface, skin and vaginal temperatures of the heifers every five minutes. The respiratory rate and the shade-use behavior were also monitored by two observers. These measurements were taken from 08:00 to 17:00 h for 18 consecutive days. After completing the field study, the heifers underwent for assessments of the daily oscillations of eCH4 emission using a flow-through respirometry system. The use of shade by the heifers was progressively increased (p < 0.01) with an increasing level of solar irradiance. Lying and ruminating were more likely (p < 0.01) to occur when the heifers were in the shade, especially when the solar irradiance exceeded 500 W m−2. Between 10:00 and 14:00 h, the heifers benefited from the shade produced by the solar panels, with a reduction of 40% in the radiant heat load. With an increasing intensity of solar irradiance, body surface temperature, skin temperature and respiratory rate of the heifers in the shade were lower (p < 0.01) compared to when they were exposed to the sun. The heifers had a daily methane emission total of 63.5 g per animal−1 or 1.7 kg of CO2-eq. Based on this emission rate and the amount of CO2-eq that was not emitted to the atmosphere due to the electricity generated by solar panels, 4.1 m2 of panels per animal (nominal power = 335 W) would be expected to obtain a net-zero eCH4 emission. Over a period of one year (from September 2018 to August 2019), a set of ten photovoltaic panels used in the study produced 4869.4 kWh of electricity, thereby saving US $970.00 or US $48.00 per m2 of solar panel. Based on the results of this study, it can be concluded that use of Animal Agrivoltaics, in addition to producing electricity, has significant potential benefit in providing better thermal comfort to cattle, as well as offsetting the enteric methane emissions released into the environment. In addition, the system would provide extra income to farmers, as well as a potential source of energy micro-generation.